2021
DOI: 10.1371/journal.pone.0243292
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics analysis reveals the molecular mechanism of enhanced cold tolerance through ROS scavenging in winter rapeseed (Brassica napus L.)

Abstract: Two winter rapeseed cultivars, “NS” (cold tolerant) and “NF” (cold sensitive), were used to reveal the morphological, physiological, and proteomic characteristics in leaves of plants after treatment at -4°C for 12 h(T1) and 24 h(T2), and at room temperature(T0), to understand the molecular mechanisms of cold tolerance. Antioxidant activity and osmotic adjustment ability were higher, and plasma membrane injury was less obvious, in NS than in NF under cold stress. We detected different abundant proteins (DAPs) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The two extension winter rapeseed cultivars in Northwest China, freezing-resistant cultivar 17NTS57 (NS, with more than 85% overwinter survival rate at −26°C, dark brown seed, 33.02% oleic acid, and 17.29% linoleic acid) and freezing-sensitive cultivar NQF24 (NF, with 0% overwinter survival rate below −10°C, dark brown seed, 36.98% oleic acid, and 16.73% linoleic acid), used in this study were provided by Gansu Agricultural University ( Mi et al, 2021 ). The seedlings of the two cultivars were grown in plastic pots (5 L) filled with soil and normally maintained.…”
Section: Methodsmentioning
confidence: 99%
“…The two extension winter rapeseed cultivars in Northwest China, freezing-resistant cultivar 17NTS57 (NS, with more than 85% overwinter survival rate at −26°C, dark brown seed, 33.02% oleic acid, and 17.29% linoleic acid) and freezing-sensitive cultivar NQF24 (NF, with 0% overwinter survival rate below −10°C, dark brown seed, 36.98% oleic acid, and 16.73% linoleic acid), used in this study were provided by Gansu Agricultural University ( Mi et al, 2021 ). The seedlings of the two cultivars were grown in plastic pots (5 L) filled with soil and normally maintained.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the gene expression in response to cold stress may be regulated by redox signaling, as several defense genes containing antioxidant-responsive elements in their promoter regions [88]. More recently, the proteomics analysis in Brassica napus L. showed that the molecular mechanism of enhanced cold tolerance was achieved through ROS scavenging via the metabolic pathways [166].…”
Section: Role Of Ros During Low Temperatures Stressmentioning
confidence: 99%
“…Over the past decade, our research group has successfully selected and bred rapeseed cultivars of B. napus that can overwinter safely in most of the northwestern areas from the 38° to the 42° north latitude, where the lowest temperature in winter is -26℃ [15,16]. Moreover, the cold tolerance characteristics of these rapeseed cultivars at the transcription, protein, physiological, biochemical, and subcellular levels were studied [15,21,22]. The strong coldresistant cultivar had stronger antioxidant enzyme activity and accumulation of cryoprotective molecules, associated with the metabolic pathways, including alpha-linolenic acid metabolism, plant hormone signal transduction, microbial metabolism in diverse environments, linoleic acid metabolism, phenylpropanoid biosynthesis, glutathione metabolism, flavonoid biosynthesis metabolism, and amino acid metabolism.…”
Section: Discussionmentioning
confidence: 99%